The Evolution of Patient Safety Practices Over the Last Two Decades - Syeda Maryam Kazmi; Muhammad Osama Khan; Syed Nabeel Safdar; Sharjeel Ahmad; Kinzah Razzak Ghazi; Saqib Kamran Bakhshi (Journal of the Pakistan Medical Association, 2026)
Patient safety has undergone significant evolution over the past two decades, driven by a shift towards systemsbased approaches, the adoption of technological solutions, and a growing global commitment to improving healthcare outcomes. Early milestones (2000- 2010) saw the establishment of key safety protocols, including the "To Err is Human" report and the World Health Organisation’s global initiatives. The following decade (2011-2020) marked the widespread integration of electronic health records and simulation-based training. The coronavirus disease-2019 pandemic presented unique challenges, including healthcare resource shortages and increased errors, but also accelerated innovations, such as telehealth and clinical decision-support tools. More recently, artificial intelligence has emerged as a powerful tool for enhancing patient safety, offering predictive capabilities and personalised care. However, barriers such as organisational resistance, resource constraints and inconsistent data-collection remain. Looking ahead, fostering a culture of safety, collaboration and continuous innovation is essential to address systemic gaps, and to ensure safer healthcare practices globally. Keywords: Patient safety; healthcare quality; electronic health records; artificial intelligence; COVID-19 pandemic